Investigating the Intraday Interdependence Between the Index Futures and Stock Index at Different Time Scales : Evidence from Bursa Malaysia - Kunle-Ogunlusi, Nene (2016)
This study examines the intraday dynamic association between the Bursa Malaysia futures and its underlying spot markets. Specifically, the study focuses on the price discovery concept and volatility transmission mechanism between the FKLI futures and the FBMKLC index using three high-frequency (10 minutes, 30 minutes and 1 hour time-scales) intraday data sets over two sample periods covering June 04, 2013 to September 30, 2013 and May 12, 2015 to June 10, 2015. The cointegration tests, VECM, Granger Causality test, variance decomposition, impulse response and bivariate GARCH model with BEKK specifications are employed in the analysis. Empirical findings signify the presence of a long-run equilibrium relationship between the futures and spot prices at all the different intraday time-scales. It is also found that new information is first incorporated in the futures prices before the spot prices. Hence, the futures market serves the price discovery function implying that when there is a shock to the system leading to a temporal short-term disequilibrium, it is the spot market that adjusts to restore equilibrium. However, the rate of adjustment to equilibrium increases with increasing time-scale from 10 minutes to 1 hour. The causality test reveal a unidirectional causality from the futures market to the spot market at all time-scales, while a bidirectional volatility transmission with more predominant spillovers from the futures market to the spot market is detected. Generally, this study has shown that the traditional financial theory of efficient market hypothesis is rejected in the case of the Bursa Malaysia FKLI futures index and FBMKLCI index. Thus, investors could use the futures prices as unbiased predictors of future spot prices. The results in this study have practical implications for all market participants and financial sector regulators.